Hydrodynamic Effects of the Length and Angle of the Ducted Propeller - Majdfar, Sohrab; Ghassemi, Hassan; Forouzan, Hamid (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
Ducted propellers used in many vessels, especially fishing vessels, trawlers and submarine which provide the higher efficiency. In this article, the effects of the duct length and duct angle are investigated on the hydrodynamic performance. First, did the modeling of duct 19A. The Kaplan propeller performance with nozzle 19A by turbulence model of SST-K-w analyzed and validated with experimental results that indicate acceptable accuracy. Finally, by changing the nozzle at a rate of 10% and 20% of the original length of the nozzle and also change the angle of the nozzle, analyzed the effects of the changes made. The Kaplan propeller with 19A nozzle is selected for case study. A Reynolds Average Navier-Stokes (RANS) turbulence model of the SST-K- w employed for the present calculations. Numerical results are included pressure distribution, hydrodynamic characteristics and velocity behind the propeller at various geometry and physical conditions. Comparisons of the results are shown with acceptable agreement by the experimental data. It is concluded that the position of the propeller and increasing the duct angle inside the duct may be limited.